The Implementation of Green Human Resource Management (Green HRM) in Supporting Sustainable Construction Projects - FA. Luky Primantari; Silvia Yulita Ratih Setyo Rahayu; Zandra Dwanita Widodo (JTI: Jurnal Teknik Industri, 2025)
The construction sector plays a strategic role in economic development, but also contributes significantly to environmental degradation. The implementation of Green Human Resource Management (Green HRM) has become an essential effort in creating sustainable construction projects through environmentally oriented human resource practices. This study aims to analyze the influence of Green HRM implementation on the performance of sustainable construction projects in Central Java. A descriptive–verificative quantitative approach was employed. Data were collected through questionnaires distributed to 120 respondents, consisting of project managers, site engineers, and HR staff. The data were analyzed using multiple linear regression with the assistance of SPSS 26.0 and SmartPLS 4.0. The findings indicate that four dimensions of Green HRM—Green Recruitment & Selection, Green Training & Development, Green Performance Appraisal, and Green Employee Involvement significantly affect project performance. In contrast, Green Compensation & Reward shows no significant effect. The coefficient of determination of 0.671 indicates that Green HRM explains 67.1% of the variation in project performance. The study concludes that Green HRM plays a crucial role in improving resource efficiency, compliance with environmental standards, and overall construction project effectiveness. Strengthening green work culture and implementing environmentally based reward systems are recommended to enhance the sustainability of Indonesia’s construction sector. Keywords: Green HRM, sustainable construction, project management, human resources